Left Inferior Vena Cava Associated with Nutcracker Phenomenon - Ulusan, Şerife; Koç, Zafer (Fırat University, 2007)
Left inferior vena cava (LIVC) is a congenital vascular malformation characterized by crossing over to the right via the left renal vein or more inferiorly crossover. The nutcracker phenomenon is defined as entrapment of the left renal vein between the aorta and superior mesenteric artery. The association between the nutcracker phenomenon and LIVC has not been reported previously. We report the radiologic and clinical findings of LIVC and nutcracker phenomenon. ©2007, Fırat Üniversitesi, Tıp Fakültesi

Sol inferior kava, inferior vena kavanın sol renal veni verirken veya daha distal düzeyde sağdan, sol tarafa geçmesiyle karakterize konjenital vasküler bir malformasyondur. Nutcracker Fenomeni ise sol renal venin aorta ile superior mesenterik arter arasında sıkışması olarak tanımlanır. Nutckracker Fenomeni ile sol inferior vena kava birlikteliği daha önce tanımlanmamıştır. Bu yazımızda Nutckracker Fenomeni ile sol inferior vena kavanın klinik ve radyolojik bulgularını sunmayı amaçladık. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Sol İnferior Vena Kava'ya Eşlik Eden Nutcracker Fenomeni